Pulmonary capillary hemangiomatosis: a case series and review of literature - Abdelnabi, Mahmoud (Am J Cardiovasc Dis, 2021)
Pulmonary capillary hemangiomatosis (PCH) is a rare cause of pulmonary hypertension (PH) of unknown etiology resulting from pulmonary capillary proliferation. Clinically, PCH is seen in young adults with equal sex predilection and rarely reported familial predisposition. PCH’s main clinical presentations are progressive dyspnea, fatigue, hemoptysis, palpitations, and later irreversible pulmonary hypertension and right-sided heart failure. Hereby, we report three PCH cases, each case presented with a peculiar presentation with a comprehensive literature review highlighting etiology, clinical presentations, diagnostic modalities and pathology in establishing a diagnosis, current treatment options, and prognosis of PCH. In conclusion, defining PCH as the underlying cause of PH is of utmost importance as most medications used for PH are ineffective in PCH. Vasodilators should be avoided due to the increased risk of pulmonary oedema. Pathological examination of the lung is still considered the most definitive diagnostic tool, yet it is associated with complications risk. High-Resolution Computed Tomography (HRCT) chest is currently considered the cornerstone non-invasive modality for the diagnosis of PH. So far, no definitive treatment of PCH excluding lung transplantation with preliminary promising results with angiogenesis Inhibitors. PCH carries a very poor prognosis with a median survival of 3 years from the time of diagnosis.